The effects of a high carbohydrate diet on cortisol and salivary immunoglobulin A (s-IgA) during a period of increase exercise workload amongst Olympic and Ironman triathletes - Costa, R. J. S.; Jones, G. E.; Lamb, K. L.; Coleman, R.; Williams, J. H. H. (International Journal of Sports Medicine, 2005)
The present study observed the effects of a 6-day high carbohydrate (H-CHO) diet on salivary cortisol and IgA during a period of increased exercise workload. Thirty-two competitively trained male triathletes were randomly allocated into a self-selected (SS), or an H-CHO (12 g CHO kgbm-1 · day-1) dietary group. In addition to their training regimes, all subjects performed a 1-hour running exercise bout at 70 % V·O2max · d-1, for six days. Saliva samples were taken pre, immediately post, and morning post-exercise bout on days 1, 4, and 6. The concentrations of s-IgA and cortisol were determined by ELISA assays. There was a significant (p < 0.001) interaction between Group × Time for cortisol, with a marked increase in concentrations occurring in the SS dietary group pre to post exercise, and pre to morning post-exercise (p < 0.01). Conversely, a significant (p = 0.009) Group × Time interaction reflected higher post exercise s-IgA concentrations (p < 0.005) than pre exercise in the H-CHO diet group. Blood glucose concentration decreased pre to post exercise in the SS diet group (p < 0.01), whilst remaining stable in the H-CHO group. It is concluded that the consumption of a high CHO diet throughout a 6-day period of overtraining had a favourable effect on markers of immune activity and thereby reduced the susceptibility of these endurance athletes to upper respiratory tract infection URTI.